Floating-Harbor syndrome ‒ case report with literature review - Popov, Trifon T.; Yaneva, Natasha Y. (Rzeszów University Press, 2026)
Introduction and aim. Floating-Harbor syndrome (FHS) is a very rare disease, whose typical characteristics include short stature, facial dysmorphic features and significant speech delay. We aim to present the first reported case of FHS with discordant growth hormone tests and confirmed hypoplasia of the pituitary gland. Description of the case. We report a case of a boy aged 8 years and 3 months with a height constantly below the 3rd percentile, delayed bone age in comparison to chronological age, typical dysmorphic triangular face and a high-pitched voice. Whole-exome sequencing (WES) detected a heterozygous pathogenic variant in SRCAP gene – a confirmation of the diagnosis Floating-Harbor syndrome (FHS). Recombinant human growth hormone (rhGH) therapy at a dose of 0.033 mg/kg/day (0.65 mg/day) was initiated at the age of 7 years and 10 months. Because of the insufficient growth velocity at the time of manuscript preparation a dose increase was made to 0.035 mg/kg/day (0.80 mg/day). Conclusion. In children presenting with short stature (especially when GH deficiency is confirmed), facial dysmorphism and developmental delay, Floating-Harbor syndrome should be considered as a possible diagnosis. A multidisciplinary approach involving pediatric endocrinologists, geneticists and developmental specialists is essential for timely etiological diagnosis and optimal management.
The study was conducted following the regulations of the Hospital and Medical University – Sofia, as well as General Data Protection Regulation (GDPR). Written informed consent was obtained from the parent of the patient for publication of this article and any accompanying images.
Keywords: Floating-Harbor syndrome; short stature; recombinant human growth hormone treatment